THE EFFECTIVENESS OF SMARTPHONE USE IN ENHANCING BILINGUAL SKILLS OF MIDDLE SCHOOL STUDENTS - Erick, Erick Saut Maruli Sihombing; Bernieke Anggita Ristia Damanik (Sindoro: Cendikia Pendidikan, 2025)
This research aims to explore and assess the impact of smartphone usage in English language learning. The study focuses on aspects such as making students more motivated, helping them work together, and the ease of carrying smartphones anywhere. The researchers looked at how smartphones help students learn English bettter by using interviews and questionnaires. The study focused on English language education students from SMP CR 2, with twenty students who owned smartphones participating as research subjects. Researchers used interviews and questionnaries as their methods of data collection. The students’ perceptions revealed that using smartphones influenced their motivation, mobility and ability to collaborate while learning English. Moreover, smartphones were seen as tools that could enhance their effectiveness in learning English. There findings align with Barker’s theory about the positive effects of smartphones use in language learning. However, there were also some negative aspects, such as the potential for students to use smartphones to cheat due to their easy of carring smartphones anywheere, their tendency to seek quick solution, and the risk of developing an addiction to their devices.